PROFITABILITY OF SMALL- SCALE RICE PROCESSING IN KUMBOTSO LOCAL GOVERNMENT AREA OF KANO STATE, NIGERIA - Ishaya, R. G.; Egwuma, H.; Gomina, A.; Uchendu, C. U.; Ojewumi, J. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the cost structure, returns, and profitability of small-scale rice processing in Kumbotso Local Government Area of Kano State, Nigeria. Primary data were collected from 90 small-scale rice processors using structured questionnaires and analyzed using descriptive statistics and farm budgeting techniques. The results revealed that rice processing in the study area is predominantly male-dominated (88.89%), with processors having an average age of 34 years and an average household size of eight members. Most (66.67%) processors possessed at least basic formal education and had an average processing experience of eight years, with mean monthly income of ₦196,667. The cost and returns analysis showed that the total cost of rice processing was ₦1,732,809 per month, with total variable cost accounting for 94.84% and total fixed cost representing 5.16% of the total cost. The purchase of paddy rice constituted the largest share of the total processing cost (63.48%), followed by processing charges (27.93%). The total revenue generated from 44 bags (100 kg bags) was ₦2,098,500, with a net processing income of ₦365,691 per month, a return on investment of 0.21, an operating ratio of 0.78 and a benefit–cost ratio of 1.21. Critical constraints to rice processing enterprise include poor transportation networks (97.8%), inadequate storage facilities (96.7%), unreliable power supply (94.4%), inadequate capital (93.3%), limited technical knowledge and skills (85.6%), and reliance on outdated processing equipment (81.1%). Our research highlights the important role of small-scale rice processing as a profitable business that helps generate income and improve rural livelihoods. Accordingly, improving rural infrastructure, expanding access to affordable credit, modernising storage systems, and carrying out targeted capacity-building initiatives should be the pivot of policy interventions. In this way, the efficiency and long-term sustainability of rice processing enterprises in the study area will be improved.